1991
DOI: 10.1016/0378-1135(91)90079-u
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the epizootiology of feline enteric coronavirus and the pathogenesis of feline infectious peritonitis

Abstract: This review presents some current thoughts regarding the epizootiology of the feline coronaviruses; feline infectious peritonitis virus (FIPV) and feline coronavirus (FECV) with primary emphasis on the pathogenesis of these viruses in nature. Although the mechanism(s) whereby FIPV causes disease are still incompletely understood, there have been significant contributions to the literature over the past decade which provide a framework upon which plausible explanations can be postulated. Two concepts are presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…The genome of some FECV strains proved to be 0.3 kb shorter, suggesting a deletion of 300 bp at the 3 -end (Vennema et al, 1992). Molecular studies showed that FIPV arises by mutation from FECV (Pedersen et al, 1981;Evermann et al, 1991;Hök, 1993;Poland et al, 1996;Herrewegh et al, 1997;Vennema et al, 1994Vennema et al, , 1998. Both FIPV and FECV may, depending on their virulence, cause viremia (Herrewegh et al, 1995;Fehr et al, 1996;Gunn-Moore et al, 1998;Horzinek, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The genome of some FECV strains proved to be 0.3 kb shorter, suggesting a deletion of 300 bp at the 3 -end (Vennema et al, 1992). Molecular studies showed that FIPV arises by mutation from FECV (Pedersen et al, 1981;Evermann et al, 1991;Hök, 1993;Poland et al, 1996;Herrewegh et al, 1997;Vennema et al, 1994Vennema et al, , 1998. Both FIPV and FECV may, depending on their virulence, cause viremia (Herrewegh et al, 1995;Fehr et al, 1996;Gunn-Moore et al, 1998;Horzinek, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…FeCoV are known for their considerable variability. It has been demonstrated that FIP can develop as a result of mutation of FeCoV in the intestine of cats affected by coronavirus-induced enteritis (Evermann et al 1991). Outbreaks of FIP can occur also in colonies where not a single case was recorded in the past.…”
mentioning
confidence: 99%
“…In other words, one could identify an isolate as FIPV or FECV, regardless of clinical conditions of the cat from which it was isolated, only after experimental determination of its disease-causing potential in cats. FECV is epizootiologically the predominant FCoV in the field, and it has been tentatively concluded that FIPV is a mutant of FECV, though the exact mutation mechanism has yet to be clarified [4,21,23,29].…”
Section: Methodsmentioning
confidence: 99%
“…In other words, one could identify an isolate as FIPV or FECV, regardless of clinical conditions of the cat from which it was isolated, only after experimental determination of its disease-causing potential in cats. FECV is epizootiologically the predominant FCoV in the field, and it has been tentatively concluded that FIPV is a mutant of FECV, though the exact mutation mechanism has yet to be clarified [4,21,23,29].FCoVs are divided into two distinct serotypes I and II by neutralization specificities induced by a spike protein [5,10,11,19]. Serotype I FCoV isolates have been numerically superior [22] and predominantly distributed among cats [9].…”
mentioning
confidence: 99%